Systemic and Local CC Chemokines Production in a Murine Model of <emph>Listeria monocytogenes</emph> Infection (Mediators of Inflammation)
Repeated intragastric inoculation of <emph>Listeria monocytogenes</emph> into BALB/c mice resulted in prolonged bacteraemia and severe hepatic infection. Bacteria could also be isolated from the brain tissue of all experimental mice. During the inflammatory process, chemokine concentrations typically increased at the local site in comparison to the systemic level. The liver-to-serum ratio was more pronounced in the case of macrophage inflammatory protein 1 α (MIP-1 α ), suggesting its role in the inflammatory response in the liver. The ratio of brain-to-serum concentration of monocyte chemoattractant protein 1 (MCP-1) remained the same as in the control animals, while it was lower in the infected mice, both in the case MIP-1 α and in the case of regulated on activation, normal T cell expressed and secreted (RANTES). This is in correlation with slight inflammatory infiltrates found in the brain tissue early in infection.